2015
DOI: 10.1248/bpb.b14-00669
|View full text |Cite
|
Sign up to set email alerts
|

Anti-stress Effects of 20(<i>S</i>)-Protopanaxadiol and 20(<i>S</i>)-Protopanaxatriol in Immobilized Mice

Abstract: Stress is a common and unavoidable phenomenon in human life.1,2) Exposure to stress induces glucocorticoid release via the activation of the hypothalamo-pituitary-adrenal (HPA) axis and it modulates immune cells and further modulates cytokine production.3-5) Among these cytokines, proinflammatory interleukin (IL)-6 and tumor necrosis factor (TNF)-α are up-regulated by stress and are associated with host defense systems.6) The failure to cope with stress exacerbates both psychological and immune disorders, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Compound 4 is an effective compound, and earlier researches have confirmed that it had significant effects, including cardioprotective [21] and antiobesity bioactivities [22]. In recent years, neuroprotective effects of compound 4 were also reported [23,24]. However, this study was the first to evaluate its effects on NDs in an in vitro experimental model.…”
Section: Discussionmentioning
confidence: 84%
“…Compound 4 is an effective compound, and earlier researches have confirmed that it had significant effects, including cardioprotective [21] and antiobesity bioactivities [22]. In recent years, neuroprotective effects of compound 4 were also reported [23,24]. However, this study was the first to evaluate its effects on NDs in an in vitro experimental model.…”
Section: Discussionmentioning
confidence: 84%
“…Qiang et al reported that, after oral administration, Rb1, Rc, Rb2, Rb3 are mainly metabolized to compound K via Rd by gut microbiota (Qiang et al, ). Orally administered ginsenoside Rb1 and Re are metabolized to compound K via ginsenoside Rd and PPT and Rh1 via Rg1 by gut microbiota (Oh, Kim, Choi, Kim, & Kim, ). Wang et al reported that Rg1 and Re are converted to Rh1 and F1 by gut microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…PNS (58.6%) significantly decreased immobility time in the forced swim test with little effect on locomotion in the chronic mild stress model, and significantly improved the level of animal activity and sucrose consumption [67], which may have antidepressant-like effects [45,53,64,65],. Besides, when PNS was digested by Snail Enzyme to 50%, it produced the best antidepressant effects, and the main active ingredient is ginsenosides Rb1, Rb2, Rc and Rb3 [60,[68][69][70][71]. These were shown in table 1.…”
Section: Mechanisms Of Antidepression 21 Panax Notoginseng Saponinsmentioning
confidence: 96%
“…Recent studies have found that Panax notoginseng saponins (PNS) have good preventive and therapeutic effects on neurological diseases of the brain [28], especially in antidepressant [26][27][28] and anti-anxiety effects [25,28,40]. The preliminary determination was that anti-depressant and anti-anxiety effects may occur by increasing the levels of the brain monoamine neurotransmitters 5-hydroxytryptamine (5-HT) [41,42] and norepinephrine (NE) in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%